Liquidations and receiverships a look at tax planning and tax implications / Hasnol Esa - Hasnol, Esa (1988)
It is important firstly to understand the circumstances leading to liquidation of a company, or it being placed under receivership : Circumstances leading to companies being wounded up or placed under receivership. Continual losses on trading due to one or more of these factors. Sudden and unresolved cash flow problem due to one or more of these factors.